2017
DOI: 10.52321/geolbalc.46.2.73
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater contribution to the river flow for the upper course of the Osam River based on two baseflow separation methods

Abstract: The study area in the upper part of the Osam River basin (central North Bulgaria) is characterized by highly variable mountain relief and diversified geological and hydrogeological conditions. Mesozoic clayey-terrigenous sediments are widespread in the area. Triassic and Jurassic carbonate rocks are developed locally, mainly in the upper part of the river basin. The mountainous landscape is dominated by old-forest vegetation communities. Both fissured-porous and karst groundwater systems are developed in the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…An Indonesian study has estimated BFI values for karst springs up to 0.9 (Fatchurohman et al 2018). Vasileva et al (2017) used a BFI of 0.8 for Bulgarian karst systems, while the UK baseflow index is set at 0.9 for chalk (UK_CEH 2022)-for example, in the Pang and Lambourn river catchments in southern England, the BFI indexes were calculated to be 0.87 and 0.96, respectively (Maurice et al 2006;Maurice 2009). However, the research reported here shows that the criteria limits that distinguish karst streams from nonkarst streams are not universal and can likely not be transferred to other parts of Denmark or abroad.…”
Section: Discussionmentioning
confidence: 99%
“…An Indonesian study has estimated BFI values for karst springs up to 0.9 (Fatchurohman et al 2018). Vasileva et al (2017) used a BFI of 0.8 for Bulgarian karst systems, while the UK baseflow index is set at 0.9 for chalk (UK_CEH 2022)-for example, in the Pang and Lambourn river catchments in southern England, the BFI indexes were calculated to be 0.87 and 0.96, respectively (Maurice et al 2006;Maurice 2009). However, the research reported here shows that the criteria limits that distinguish karst streams from nonkarst streams are not universal and can likely not be transferred to other parts of Denmark or abroad.…”
Section: Discussionmentioning
confidence: 99%